Genome-Wide Approaches to Schizophrenia - Duan, Jubao (2010)
Schizophrenia (SZ) is a common and severe psychiatric disorder with both environmental and genetic risk factors, and a high heritability. After over 20 years of molecular genetics research, new molecular strategies, primarily genome-wide association studies (GWAS), have generated major tangible progress. This new data provides evidence for: 1) A number of chromosomal regions with common polymorphisms showing genome-wide association with SZ (the major histocompatibility complex, MHC, region at 6p22-p21; 18q21.2; and 2q32.1). The associated alleles present small odds ratios (the odds of a risk variant being present in cases versus controls) and suggest causative involvement of gene regulatory mechanisms in SZ. 2) Polygenic inheritance. 3) Involvement of rare (<1%) and large (>100kb) copy number variants (CNVs). 4) A genetic overlap of SZ with autism and with bipolar disorder (BP) challenging the classical clinical classifications. Most new SZ findings (chromosomal regions and genes) have generated new biological leads. These new findings, however, still need to be translated into a better understanding of the underlying biology and into causal mechanisms. Furthermore, a considerable amount of heritability still remains unexplained (missing heritability). Deep resequencing for rare variants and system biology approaches (e.g., integrating DNA sequence and functional data) are expected to further improve our understanding of the genetic architecture of SZ and its underlying biology.